KOMUNITAS TIONGHOA PADA PARTAI NASIONAL INDONESIA (DALAM BINTANG BORNEO TAHUN 1930 ) - Fitriani, Fitriani (Langgong: Jurnal Ilmu Sosial dan Humaniora, 2023)
The arrival of the Chinese in the archipelago has a long history of migration. The first migration pattern was huashang or trade, which started in mainland China and then expanded to Southeast Asia between the 5th and 18th centuries. Chinese nationalism intensified as a result of the establishment of residence zones (wijkenstelsel), including Chinatown villages, and the passenstelsel system. In 1930 the Chinese community participated in the Indonesian National Party (PNI) which was founded in 1927. To examine the role of the Chinese community in the Indonesian National Party movement in 1930, the historical method is used because the object of the problem is past events. To draft this research using a descriptive qualitative method with a structured narrative description, this article is also written using a literature study. Literature study is defined as a series of activities related to data collection based on library sources, reading and recording. In searching for literature, it is utilized by searching from archives in the form of newspapers and journals on the google scholar site. The rise of Indonesia's national spirit also had an influence on the Chinese. When the PNI was established, some Chinese people were interested in joining it, unfortunately according to the PNI Articles of Association, people of other Asian nations could only become extraordinary members.